Evaluation of Periodontal Health Status in Pre and Postmenopausal Women with Periodontitis - Tanu Sahney; Amitabh Srivastava; Yasir S. Khan; Vivek Srivastava; Ajita Meenawat; Vinod Kumar (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Periodontal disease is influenced by various risk factors, including hormonal changes in women, such as those occurring during menopause, which have been linked to periodontal deterioration and osteoporosis. This study assessed and compared the periodontal and gingival health of premenopausal and postmenopausal women. Methodology: In the study, thirty female patients with age between 25 and 65 years, who visited the Department of Periodontology at SPPGIDMS, Lucknow, and were diagnosed with periodontitis with pocket depths greater than 5 mm, were analyzed. The patients were divided into: Group 1 which included 15 premenopausal women diagnosed with chronic periodontitis and Group II included 15 postmenopausal women having chronic periodontitis. Oral examinations were conducted, and clinical parameters such as gingival bleeding index, plaque index (PI), and pocket probing depth (PPD) were assessed using a UNC 15 periodontal probe at four sites of each tooth. In addition, furcation involvement and other oral conditions, including xerostomia, burning mouth syndrome, caries, oral ulcers, tooth loss due to periodontitis, and bleeding gums, were also evaluated. Results: Premenopausal women showed in significant difference for plaque index, gingival index, pocket probing depth, and clinical attachment loss when compared with the postmenopausal group. The differences between the two groups were statistically significant, with a P value of 0.01. Conclusion: Postmenopausal women are more prone to periodontitis. The impact of hormonal changes on periodontal health can be mitigated through regular dental check-ups, good oral hygiene practices, and hormonal replacement therapies.